The maximum height attained by a projectile can be derived from the vertical motion component of the projectile. The vertical velocity at the maximum height is zero, and the equation of motion is:
\[
v_y^2 = u_y^2 - 2gH_{\text{max}},
\]
where:
\( u_y = u \sin \theta \) is the vertical component of the initial velocity,
\( v_y = 0 \) at the maximum height,
\( g \) is the acceleration due to gravity,
\( H_{\text{max}} \) is the maximum height.
Rearranging for \( H_{\text{max}} \), we get:
\[
H_{\text{max}} = \frac{u_y^2}{2g} = \frac{(u \sin \theta)^2}{2g}.
\]
Let the two projectiles have angles of projection:
\[
\theta_1 = 30^\circ \quad \text{and} \quad \theta_2 = 60^\circ.
\]
For the first projectile:
\[
H_1 = \frac{(u \sin 30^\circ)^2}{2g}.
\]
For the second projectile:
\[
H_2 = \frac{(u \sin 60^\circ)^2}{2g}.
\]
The ratio of their maximum heights is:
\[
\frac{H_1}{H_2} = \frac{(u \sin 30^\circ)^2}{(u \sin 60^\circ)^2}.
\]
Canceling common terms \( u^2 \) and substituting \( \sin 30^\circ = \frac{1}{2} \) and \( \sin 60^\circ = \frac{\sqrt{3}}{2} \), we get:
\[
\frac{H_1}{H_2} = \frac{\left(\frac{1}{2}\right)^2}{\left(\frac{\sqrt{3}}{2}\right)^2}.
\]
Simplify:
\[
\frac{H_1}{H_2} = \frac{\frac{1}{4}}{\frac{3}{4}} = \frac{1}{3}.
\]
Thus, the ratio of the maximum heights is:
\[
H_1 : H_2 = 1 : 3.
\]
Final Answer:
\[
\boxed{1 : 3}
\]